1997
DOI: 10.2500/105065897782537133
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Middle Meatal and Maxillary Sinus Cultures in Acute Maxillary Sinusitis

Abstract: Cultures obtained from the middle meatus have been used frequently in the past to direct therapy in patients with acute maxillary sinusitis. However, no convincing data have been published to indicate that middle meatal cultures accurately represent the bacterial flora within the maxillary sinus. The hypothesis of this experiment is that bacteria obtained by directed middle meatal cultures qualitatively and quantitatively correlate with cultures taken by maxillary sinus puncture. Acute sinusitis was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…There were no complications from either endoscopy or puncture, but it was noted that patients reported that the latter was more painful. The findings in these 3 studies [11,32,33] are consistent with observations of concordance between middle meatal and maxillary sinus cultures in a rabbit model of ABMS [34]. The current study confirms, in a larger population, the concordance between puncture and aspiration culture results and endoscopy culture results for patients with ABMS.…”
Section: Discussionsupporting
confidence: 94%
“…There were no complications from either endoscopy or puncture, but it was noted that patients reported that the latter was more painful. The findings in these 3 studies [11,32,33] are consistent with observations of concordance between middle meatal and maxillary sinus cultures in a rabbit model of ABMS [34]. The current study confirms, in a larger population, the concordance between puncture and aspiration culture results and endoscopy culture results for patients with ABMS.…”
Section: Discussionsupporting
confidence: 94%
“…Orobello et al 13 found a strong correlation between middle meatal cultures and both maxillary and ethmoid sinus cultures in children, even though gross purulence was rarely encountered in their patients. Finally, Valdya et al 16 induced acute sinusitis in 24 rabbits and demonstrated a 100% correlation between middle meatal and maxillary sinus cultures in those animals. They concluded that middle meatal cultures accurately reflect maxillary sinus pathogens and could be used to direct antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study on the effects of septoplasty on the nasal flora found that 16 per cent of patients had coagulase negative S aureus cultured postoperatively; 37 again, this would appear to represent colonisation only. 30,40,41 Other organisms grown readily from nasal swabs and mucosal specimens include Citrobacter diversus, Streptococcus viridans and Staphylococcus epidermidis. 38,39 (Middle meatal swabs would appear to be equally as valid as antral aspirates for determining the microbiological population of the maxillary antrum.)…”
Section: Discussionmentioning
confidence: 99%